PERCEPTION OF CULTURAL COMPETENCE OF ICU NURSES: A CROSSSECTIONAL STUDY - Titis Mustikowati Danasari; Yulis Setiya Dewi; Wikan Purwihantoro Sudarmadji (Journal of Vocational Nursing, 2026)
Introduction: Delivering nursing care in intensive care units has numerous challenges, one of which pertains to cultural concerns. Cultural views of nurses can obstruct the provision of holistic nursing care. This study seeks to identify characteristics related to views of cultural competency among ICU nurses. Methods: This study employed a descriptive-analytic strategy utilizing a cross-sectional approach. The study sample consisted of 208 respondents, chosen using purposive sampling. Data were collected via a questionnaire and analyzed through binomial logistic regression at a significance level of p<0.05. Results: The perception of cultural competence among ICU nurses was significantly connected with age (p = 0.008), gender (p=0.038), and both career and competency level (p=0.031). Perceptions of cultural competency among ICU nurses were often inadequate. Gender was the predominant variable. Conclusions: ICU nurses with a positive sense of cultural competency influence the enhancement of nursing care implementation and quality